2018
DOI: 10.1016/j.ymthe.2018.02.012
|View full text |Cite|
|
Sign up to set email alerts
|

Human ISL1+ Ventricular Progenitors Self-Assemble into an In Vivo Functional Heart Patch and Preserve Cardiac Function Post Infarction

Abstract: The generation of human pluripotent stem cell (hPSC)-derived ventricular progenitors and their assembly into a 3-dimensional in vivo functional ventricular heart patch has remained an elusive goal. Herein, we report the generation of an enriched pool of hPSC-derived ventricular progenitors (HVPs), which can expand, differentiate, self-assemble, and mature into a functional ventricular patch in vivo without the aid of any gel or matrix. We documented a specific temporal window, in which the HVPs will engraft in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 58 publications
5
35
0
2
Order By: Relevance
“…The grafts from primed CPCs exhibited hPSC‐CMs with elongated morphology and aligned myofilaments in contrast to the more immature appearing circular clusters of hPSC‐CMs from untreated CPCs. We cannot exclude that longer in vivo follow‐up of animals would equalize certain of these differences, but the finding of accelerated differentiation of primed CPCs is consistent with the previously reported ability of later stage, committed CPCs to more readily differentiate into hPSC‐CMs in the kidney capsule in contrast to early stage CPCs . In addition, these results from the heterotopic kidney capsule transplant model agree with the observed in vitro effects of pIC and suggest that this strategy could have relevance for cell therapy applications.…”
Section: Resultssupporting
confidence: 85%
“…The grafts from primed CPCs exhibited hPSC‐CMs with elongated morphology and aligned myofilaments in contrast to the more immature appearing circular clusters of hPSC‐CMs from untreated CPCs. We cannot exclude that longer in vivo follow‐up of animals would equalize certain of these differences, but the finding of accelerated differentiation of primed CPCs is consistent with the previously reported ability of later stage, committed CPCs to more readily differentiate into hPSC‐CMs in the kidney capsule in contrast to early stage CPCs . In addition, these results from the heterotopic kidney capsule transplant model agree with the observed in vitro effects of pIC and suggest that this strategy could have relevance for cell therapy applications.…”
Section: Resultssupporting
confidence: 85%
“…As established in a previous study in hESCs , in vitro cardiogenesis occurs via sequential distinct developmental stages, corresponding to the parental embryonic stem cells (day 0), primitive streak/early mesoderm (day 1), cardiac mesoderm (day 3), and cardiac progenitor/early CM stages (day 6). To understand the downstream effect of SMAD4 mutations in this sequential process of human in vitro cardiogenesis, we used RNA‐Seq to comprehensively compare the transcriptional profiles between the WT and the SMAD4 mutants at these stages.…”
Section: Resultsmentioning
confidence: 87%
“…Primary cardiomyocytes isolated from neonatal mice, rats, and chicken embryos were popular cell sources for in vitro cardiac models , but research based on these primary cells demonstrated that animal cell‐based models cannot truly recapitulate human physiology. Consequently, more sophisticated cell models were developed to create human‐like tissue models . However, establishing human models proved to be challenging as cardiac tissue or isolated cardiomyocytes from patients are difficult to obtain and cannot survive long‐term culture .…”
Section: Cardiac Disease Modeling—translation To the Clinical Settingmentioning
confidence: 99%
“…As a result, matured human cardiac organoids can be applied for high throughput screening. Alternatively, Foo et al have recently introduced a method for the generation of vascularized cardiac tissues by transplanting human stem cell‐derived cardiac precursors subcapsularly onto kidneys in mice . Furthermore, Lind et al demonstrated that the popular “Heart‐on‐a‐chip” concept can now be obtained by a combination of a 3D printed flexible chip and tissue engineering .…”
Section: Cardiac Tissue Engineeringmentioning
confidence: 99%